2017
DOI: 10.3389/fmicb.2017.02625
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Aspects Suggesting a “Fluxus” of Information in the Virions of Herpes Simplex Virus Populations

Abstract: Our perspective on nature has changed throughout history and at the same time has affected directly or indirectly our perception of biological processes. In that sense, the “fluxus” of information in a viral population arises a result of a much more complex process than the encoding of a protein by a gene, but as the consequence of the interaction between all the components of the genome and its products: DNA, RNA, and proteins and its modulation by the environment. Even modest “agents of life” like viruses di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Multinucleated cells forming a syncytium due to the fusion of adjacent infected cells were also observed. Also, in this passage, a marked change was detected in the size of the viral plaques, coexisting small viral plaques (1 mm) (similar to the parental strain) and large viral plaques of 1.5-2 mm, until passage 16, from which homogeneity of large plaques as syncytium was maintained [10]. When viral titer decreases in 1.5-2 log (Figure 1) a viral amplification was performed using minimal amount of CGN.…”
Section: Symphonic Poem Of 100 Metronomes and The Experimental Modelmentioning
confidence: 97%
See 2 more Smart Citations
“…Multinucleated cells forming a syncytium due to the fusion of adjacent infected cells were also observed. Also, in this passage, a marked change was detected in the size of the viral plaques, coexisting small viral plaques (1 mm) (similar to the parental strain) and large viral plaques of 1.5-2 mm, until passage 16, from which homogeneity of large plaques as syncytium was maintained [10]. When viral titer decreases in 1.5-2 log (Figure 1) a viral amplification was performed using minimal amount of CGN.…”
Section: Symphonic Poem Of 100 Metronomes and The Experimental Modelmentioning
confidence: 97%
“…Surprisingly, a preliminary study of structural and nonstructural genes of the variants by Next Generation Sequencing (NGS) revealed that, in addition to the glycoproteins, the variants have altered genes that would not be related to the target of action of CGN as thymidine kinase and viral DNA polymerase [10,11]. These genes are responsible for pathogenicity and virulence.…”
Section: Symphonic Poem Of 100 Metronomes and The Experimental Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…For this recognition to occur, the mask of ego must fall and give way to soul forces (consciousness).This incorporation process is not governed by doctrine principles, by ceremonial formulas or by institutional forms, but by universal and sacred life laws. Human beings around the world, from different social and cultural conditions, are not only spiritual forces, but are also social fabrics, that invisible fabric that serves as physiological support for future humanity, where viruses, their components and regulators (prophages, proviruses) play a fundamental role in dynamics and evolutionary stability of living systems [12,13,14]. This is where these brand new human traits come from.…”
Section: Nature and Meaning Of Human Existential Crisismentioning
confidence: 99%
“…But if we also take into account its capacity for self-repair, both at the cellular and embryological level, what field of action remains for Natural Selection for changes in organisms that really involve evolution? [19,20,21].…”
Section: Viruses and Evolutionmentioning
confidence: 99%